On the sensations of tone as a physiological basis for the theory of music - Helmholtz, Hermann Ludwig Ferdinand von, 1821-1894 (New York : Dover Pub, 1954)
Translation of Die Lehre von den Tonempfindungen
Includes index
Keywords: Sound; Music -- Physiological aspects; Music -- Accoustics and physics